2022
DOI: 10.7717/peerj.13522
|View full text |Cite
|
Sign up to set email alerts
|

Full-genome sequencing and mutation analysis of SARS-CoV-2 isolated from Makassar, South Sulawesi, Indonesia

Abstract: Introduction A global surge in SARS-CoV-2 cases is occurring due to the emergence of new disease variants, and requires continuous adjustment of public health measures. This study aims to continuously monitor and mitigate the impact of SARS-CoV-2 through genomic surveillance, to determine the emergence of variants and their impact on public health. Methods Data were collected from 50 full-genome sequences of SARS-CoV-2 isolates from Makassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
(52 reference statements)
0
7
0
1
Order By: Relevance
“…This trend aligns with previous studies that found Indonesia-associated variants (B.1.466.2 and B.1.470) were widespread before the Delta outbreak. These local variants were subsequently outcompeted by Delta lineages AY.23 and AY.24 [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend aligns with previous studies that found Indonesia-associated variants (B.1.466.2 and B.1.470) were widespread before the Delta outbreak. These local variants were subsequently outcompeted by Delta lineages AY.23 and AY.24 [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the G142D mutation was observed in the BI, PVS, and BI + PVS groups ( Figure 4 ). It has been reported that this mutation is associated with a milder Delta infection in Makassar, Indonesia [ 11 ]. This mutation affects the super-site epitope in the NTD of the S protein, which binds to NTD-targeted neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, false‐negatives can occur due to mutations in the primer target region of the SARS‐CoV‐2 genome [24]. This study used the N gene that codes nucleocapsid protein as the target region because of its plentiful mRNA contents [14], yet further study needs to be done as another recent study at the same centre found a mutation at the N protein of all their samples [28]. Besides the ambiguity of the orange colour interpretation, the LoD difference between the colorimetric and gel electrophoresis methods in this study also shows the limitation of the colorimetric method.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequencing mampu mendeteksi perubahan asam nukleat yang terjadi pada semua gen sehingga metode tersebut dijadikan sebagai metode monitoring perkembangan dan persebaran SARS CoV-2 di suatu wilayah. Beberapa penelitian menunjukan bahwa metode Whole Genome Sequencing berhasil dilakukan sebagai studi mengenai genome virus SARS CoV-2 untuk melihat mutasi, mapping persebaran hingga deteksi beberapa varian baru (Gunadi et al, 2020;Massi et al, 2022). Di Indonesia, metode whole genome sequencing masih sangat jarang sekali dilakukan.…”
Section: Pendahuluanunclassified